Emotional Freedom Tehcniques and Psychological Response of Mother Post Partum Survivor Covid 19 - Simbolon, Ganda Agustina Hartati; Sitohang, Tiur Romatua (Universitas Aisyah Pringsewu, 2022)
As a long-term psychological consequence, postpartum mothers who survive COVID-19 may have psychological symptoms such as increased stress, uncertainty, sorrow, worry, and depression. Several studies have shown elevated levels of stress, anxiety, and depressed symptoms, including suicidal ideation, in pregnant and postpartum women throughout the globe during the COVID-19 pandemic. In a similar research, EFT counseling resulted in a substantial reduction in anxiety and depression ratings among COVID-19-positive participants. The purpose of this research was to compare the psychological reactions (depression, anxiety, and stress) of postpartum moms proclaimed healed of COVID-19 before and after receiving emotional liberation methods treatment in the intervention group vs the control group.